MicroRNA181a Is Overexpressed in T-Cell Leukemia/Lymphoma and Related to Chemoresistance. (7th September 2015) - Yan, Zi-Xun; Zheng, Zhong; Xue, Wen; Zhao, Ming-Zhe; Fei, Xiao-Chun; Wu, Li-Li; Huang, Li-Min; Leboeuf, Christophe; Janin, Anne; Wang, Li; Zhao, Wei-Li
Abstract : MicroRNAs (miRs) play an important role in tumorogenesis and chemoresistance in lymphoid malignancies. Comparing with reactive hyperplasia, miR181a was overexpressed in 130 patients with T-cell leukemia/lymphoma, including acute T-cell lymphoblastic leukemia (n = 32 ), T-cell lymphoblastic lymphoma (n = 16 ), peripheral T-cell lymphoma, not otherwise specified (n = 45 ), anaplastic large cell lymphoma (n = 15 ), and angioimmunoblastic T-cell lymphoma (n = 22 ). Irrespective to histological subtypes, miR181a overexpression was associated with increased AKT phosphorylation. In vitro, ectopic expression of miR181a in HEK-293T cells significantly enhanced cell proliferation, activated AKT, and conferred cell resistance to doxorubicin. Meanwhile, miR181a expression was upregulated in Jurkat cells, along with AKT activation, during exposure to chemotherapeutic agents regularly applied to T-cell leukemia/lymphoma treatment, such as doxorubicin, cyclophosphamide, cytarabine, and cisplatin. Isogenic doxorubicin-resistant Jurkat and H9 cells were subsequently developed, which also presented with miR181a overexpression and cross-resistance to cyclophosphamide and cisplatin. Meanwhile, specific inhibition of miR181a enhanced Jurkat and H9 cell sensitivity to chemotherapeutic agents, further indicating that miR181a was involved in acquired chemoresistance. Collectively, miR181a functioned as a biomarker of T-cell leukemia/lymphoma through modulation of AKT pathway. Related to tumor cell chemoresistance, miR181a could be a potential therapeutic target in treating T-cell malignancies.